Upper limb and eye movement coordination during reaching tasks in people with stroke. Issue 20 (25th September 2018) - Meadmore, Katie L.; Exell, Timothy A.; Burridge, Jane H.; Hughes, Ann-Marie; Freeman, Christopher T.; Benson, Valerie
Abstract: Purpose: To enhance understanding of the relationship between upper limb and eye movements during reaching tasks in people with stroke. Methods: Eye movements were recorded from 10 control participants and 8 chronic stroke participants during a visual orienting task (Experiment 1) and a series of reaching tasks (Experiment 2). Stroke participants completed the reaching tasks using (i) their less impaired upper limb, (ii) their more impaired upper limb without support, and (iii) their more impaired upper limb, with support (SaeboMAS gravitational support and/or electrical stimulation). Participants were tested individually and completed both experiments in the same session. Results: Oculomotor control and the coordination between the upper limb and the oculomotor system were found to be intact in stroke participants when no limb movements were required, or when the less impaired upper limb was used. However, when the more impaired upper limb was used, success and accuracy in reaching decreased and patterns of eye movements changed, with an observed increase in eye movements to the limb itself. With upper limb support, patterns of hand-eye coordination were found to more closely resemble those of the control group. Conclusion: Deficits in upper limb motor systems result in changes in patterns of eye movement behavior during reaching tasks. These changes in eye movement behavior can be modulated by providing upper limb support. Implications for Rehabilitation: Deficits in upper limb motor systems can result in changes in patterns of eye movement behavior during reaching tasks. Upper limb support can reduce deficits in hand-eye coordination. Stroke rehabilitation outcomes should consider motor and oculomotor performance.